Lawet dance and ebleg dance: the term analysis towards its movement qualities (Harmonia: Journal of Arts Research and Education, 2017)
This study offers an insight of a research activity which focuses on art analysis, but lies its concern from the perspective of linguistics. This study is aiming at analyzing linguistic data that are related to traditional art activity to obtain further understanding beyond the existence of the art itself. Example of the activity is the linguistic analysis of terms used to label the kinds or qualities of dance movement from Central Java province, in this case are Lawet dance and Ebleg dance. Kebumen, as one of regency in Central Java, is chosen as the research location since it owns rich of typical traditional arts (local), both from the perspective of the art forms as well as the linguistic aspects. This research is analyzed by employing linguistic theory, especially the analysis of morphology and semantic. Implication of linguistic analysis done to the terms is a deep understanding towards the traditional dances being analyzed. It is further resulted in the form of identity affirmation to the traditional arts exist in the society’s environment.